1986
DOI: 10.1128/mcb.6.7.2476
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of DNA sequences coding for the Na,K-ATPase alpha-subunit in ouabain-resistant C+ cells.

Abstract: We have studied the mechanism of cellular resistance to cardiac glycosides in C+ cells. C+ cells were resistant to ouabain and overproduced plasma membrane-bound Na,K-ATPase relative to parental HeLa cells. Overexpression of Na,K-ATPase in C+ cells correlated with increased ATPase mRNA levels and amplification (approximately 100 times) of the ATPase gene. Growth of C+ cells in ouabain-free medium resulted in a marked decline in ATPase mRNA and DNA levels. However, when cells were reexposed to ouabain, they pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
1

Year Published

1987
1987
1997
1997

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 20 publications
0
15
0
1
Order By: Relevance
“…The largest amounts were found in kidney, the smallest in liver. Two or even three (r2 mRNAs (5.3-6, 3.4-4.5 and 2.4 kb) were found in different amounts in many rat tissues except for liver [61,62,64,65]. This variety could result from the differential use of the polyadenylation signals in the 3 '-untranslated region of cu2 mRNA [61].…”
Section: Tissue-specificity Of Expression Of Various Isoforms Of Na+mentioning
confidence: 99%
See 1 more Smart Citation
“…The largest amounts were found in kidney, the smallest in liver. Two or even three (r2 mRNAs (5.3-6, 3.4-4.5 and 2.4 kb) were found in different amounts in many rat tissues except for liver [61,62,64,65]. This variety could result from the differential use of the polyadenylation signals in the 3 '-untranslated region of cu2 mRNA [61].…”
Section: Tissue-specificity Of Expression Of Various Isoforms Of Na+mentioning
confidence: 99%
“…This variety could result from the differential use of the polyadenylation signals in the 3 '-untranslated region of cu2 mRNA [61]. But one cannot rule out some crosshybridization due to the high level of homology of different isoforms especially when large cDNA probes have been used [64,65]. Both main mRNAs of aI1 form have been shown to be expressed in brain, skeletal muscles and heart [61].…”
Section: Tissue-specificity Of Expression Of Various Isoforms Of Na+mentioning
confidence: 99%
“…HeLa cells, an epithelial cell line derived from human cervix, have only one alpha isoform of around 3.7 kb (Cutler et al 1988), probably equivalent to al in rat (Emanuel et al, 1986), so that the phirmacological properties of the glycosideNa+, K+-ATPase interaction of these cells can be unambiguously related to this isoform. It is of particular interest to study this isoform for we had long noticed that the effect of cardiac glycosides on these and other cultured human cells under equilibrium conditions (see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Chromosomal mapping studies revealed that the three (x subunit isoforms are encoded by separate genes, each of which is located on a different murine chromosome (18). Both ouabain resistance and the murine Na,K-ATPase al subunit gene have been assigned to mouse chromosome 3 (18,20). Gene transfer experiments have shown that rat and mouse Na,K-ATPase otl subunit * Corresponding author.…”
mentioning
confidence: 99%